4t-6=5(t+5)

Simple and best practice solution for 4t-6=5(t+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t-6=5(t+5) equation:


4t-6=5(t+5)

We simplify the equation to the form, which is simple to understand
4t-6=5(t+5)

Reorder the terms in parentheses
4t-6=+(+5t+25)

Remove unnecessary parentheses
+4t-6=+5t+25

We move all terms containing t to the left and all other terms to the right.
+4t-5t=+25+6

We simplify left and right side of the equation.
-1t=+31

We divide both sides of the equation by -1 to get t.
t=-31

See similar equations:

| 19x+26=21 | | 4n-12=13-4n | | 13x-2(3x+6)= | | -8n+12=-4n-4 | | 2n^2+11n+10=0 | | r^2-8r-20=0 | | 7-7=18x+8x | | 3(x+8)=3x+12 | | x/2=-30+35 | | 3x+4x^2=56 | | -4+10=12x-5-11x | | 3(v-2)-5v=-2(v+2) | | 3(2x-5)=7(x+2) | | v^2+6v-7= | | -6(u+1)+8u=2(u-3) | | 5x+9x+2+x= | | -4+15=14-2-13x | | -3x=57 | | 2(x+2)=7x+4 | | -2v^2+8v+24= | | 6x^2-14x^2=0 | | (8x+12)=(5x+57) | | 4x+2(x+65)=36 | | 10x+2y=6 | | 11.3x=282.5 | | v^2+5v-6= | | 0.66x+0.83=3 | | 3x-18=30 | | C+11=-14 | | -5(3x-4)=2(x+27) | | 7x=-5 | | -(6y+1)-(-5y-8)=1 |

Equations solver categories